Modeling population‐wide testing of SARS‐CoV‐2 for containing COVID‐19 pandemic in Okinawa, Japan. (5th May 2021) - Shimizu, Kazuki; Kuniya, Toshikazu; Tokuda, Yasuharu
Abstract: To break the chains of SARS‐CoV‐2 transmission and contain the coronavirus disease 2019 (COVID‐19) pandemic, population‐wide testing has been practiced in various countries. However, scant research has addressed this topic in Japan. In this modeling exercise, we extracted the number of daily reported cases of COVID‐19 in Okinawa from October 1 to November 30, 2020, and explored possible scenarios for decreasing COVID‐19 incidence by combining population‐wide screening and/or social distancing policy. We reveal that permanent lockdown can be theoretically replaced by mass testing but sufficient target population at an adequate frequency must be mobilized. In addition, solely imposing a circuit breaker will not bring a favorable outcome in the long run, and mass testing presents implications for minimizing a period of lockdown. Our results highlight the importance of incentivizing citizens to join the frequent testing and ensure their appropriate isolation. This study also suggests that early containment of COVID‐19 will be feasible in prefectures where the mobility is low and/or can be easily controlled for its geographic characteristics. Rigorous investment in public health will be manifestly vital to contain COVID‐19. Abstract : Population‐wide testing plays a vital role in containing COVID‐19, and possible scenarios for decreasing COVID‐19 incidence by combining population‐wide screening and/or social distancing policy are explored. We reveal that mass testing that mobilizes sufficient target population at an adequate frequency will help contain the pandemic, and solely imposing a circuit breaker will not bring a favorable outcome in the long run. Also, mass testing presents implications for minimizing a period of lockdown.